2D boron nitride nanosheets for polymer composite materials - Md Golam Rasul (Nature Portfolio, 2021)
Abstract Hexagonal boron nitride nanosheets (BNNSs) are promising two-dimensional materials to boost the mechanical, thermal, electrical, and optical properties of polymer nanocomposites. Yet, BNNS-polymer composites face many challenges to meet the desired properties owing to agglomeration of BNNSs, incompatibility, and weak interactions of BNNSs with the host polymers. This work systematically reviews the fundamental parameters that control the molecular interactions of BNNSs with polymer matrices. The surface modification of BNNSs, as well as size, dispersion, and alignment of these nanosheets have a profound effect on polymer chain dynamics, mass barrier properties, and stress-transfer efficiency of the nanocomposites.